Zakat Produktif Untuk Pemberdayaan Ekonomi Umat - Thoharul Anwar, Ahmad (ZISWAF, 2018)
The purpose of this study is to know the management of productive zakat for the economic empowerment of society in LAZISNU Kudus. This study uses a qualitative approach and is described descriptively. Data collection techniques used interviews, observation, and documentation. While data analysis using data reduction, data display and verification. From the results of the study concluded that the management of productive zakat funds conducted by LAZISNU Kudus using the stages in management science. The steps in the empowerment of productive zakat by LAZISNU Kudus include data collection, supervision and supervision. There are two obstacles facing LAZISNU, internal and external factors. Among the internal factors are limited funds provided, lack of coordination, lack of adequate human resources and administrative management that is still traditional. While external factors include is still a lot of muzakki who pay zakat outside amil institutions and mustahik less know management business.